`Trust Contexts' - A Grounded Theory Study of Women's Experience of Healthcare Interactions in Pregnancy and Birth in Ireland. - Hudson, Julika Johanna (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2025)
Background: Reproductive rights are often considered in relation to reproductive choices like contraception and termination of pregnancy. However, reproductive rights are equally relevant in pregnancy and childbirth and are not limited to situations of maternal-fetal conflict. Most maternity care in Ireland is currently provided in an obstetric-led, hospital-based system. Due to complex historical, political and legal factors, pregnant women between 1983 and 2018 had limitations placed on their right to consent-to or withhold consent to treatment offered in pregnancy and childbirth. In 1983, the insertion of Article 40.3.3 in the Irish Constitution gave an equal right to life to the unborn and to the `mother', causing significant challenges to the provision of care for a pregnant woman where interventions in the fetal interest were recommended but declined by the woman. Article 40.3.3 of the Irish Constitution was repealed and replaced in 2018 to allow for the enactment of the Health (Termination of Pregnancy) Act 2018 permitting the introduction of lawful termination of pregnancy in Ireland. It is yet to be established how women experience maternity care and decision-making post repeal of the 8th amendment. Aims and objectives: The aim of this study was to generate a theory that explains the main concern of pregnant women receiving maternity care in Ireland and what the women do to resolve this concern. The theory will help to understand healthcare interactions within the Irish maternity system and how decision-making in pregnancy and childbirth can be supported. Design: The study was undertaken using classic grounded theory. Methods: Data were collected in 2022/2023 through research encounters with women in pregnancy and after birth, recruited at a hospital in Ireland for over one year. Constant comparative analysis, theoretical coding and memo-writing were used to develop the substantive theory. Results: The theory of trust contexts proposes how healthcare interactions in pregnancy and birth are framed by protocolised caring. Protocolised caring is the standardisation, fragmentation and dehumanisation of care that impacts on a woman's personal resources and her degree of vulnerability. The behaviour of women, who are mitigating their vulnerability in combination with the attitudes of healthcare providers, who are more adherent or less adherent to protocolised caring, create distinct trust contexts. `Blind trust', `nascent trust', `mutual trust' and `mistrust' emerged from the data with different consequences, normalising or challenging protocolised caring. Conclusion: The theory of trust contexts explains how when altering the context of the healthcare interaction through changing attitudes, behaviours or conditions, women's agency can be supported. This gives important new insights on caring for women in pregnancy and birth, and consent-taking more specifically. It may also have implications for how we look at the impact of structural conditions on people's ability to exercise agency in general.
APPROVED
Keywords: Grounded Theory; Pregnancy; Birth; Maternity Care; Healthcare Interactions